The use of electronic concept mapping technology to facilitate understanding of the grammatical rules of tenth-grade students in Jordan - Abu Gattam, Galia Ali (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the impact of the use of conceptual maps in facilitating the understanding of the grammatical rules among tenth basic students in the Juwaida Secondary Comprehensive School for Girls in the Hashemite Kingdom of Jordan, and in order to achieve this goal the study was applied to two groups: the control group and its number (30 students) and experimental And its number is (30 students), and the pre- test was applied to both groups, and after reassuring the application of the test in the same way, grammatical rules designed on the electronic conceptual mapping strategy were provided with the experimental group, and the traditional method of indoctrination of grammatical rules with the control group was made, and the difference appeared in understanding Those rules between students of the two groups; The results of the study showed that there is a statistically significant difference between the mean scores of the experimental and control groups, and the difference is attributed to the use of electronic concept maps in the teaching of members of the experimental group, and the study recommends the need to use electronic concepts maps to explain the Arabic grammar for tenth grade students.
Keywords: Electronic maps; tenth grade; grammatical rules; grammar